Effect of 60Co γ-rays on dried figs adsorption isotherms and thermodynamic properties - Irchad, Ahmed; Razouk, Rachid; Ouaabou, Rachida; Mouhib, Mohamed; Hssaini, Lahcen (Frontiers in Nutrition, 2022)
Irradiation is one of promising food preservation techniques, but few is known about its impact on water vapor change. Figs and dried figs are among emblematic foods of the Mediterranean diet. In this research, the impact of gamma irradiation on moisture adsorption isotherms of dried figs at increasing doses (0, 1, 1.5 and 2 kGy) was investigated. Results of moisture adsorption isotherms kinetics displayed a sigmoid shaped curve of the type II pattern for both controlled and irradiated dried figs, with a notable effect of irradiation on equilibrium moisture content that showed a decreasing pattern as irradiation dose and temperature increased. This effect was also notable on data fitting, where GAB showed the best prediction statistics for control dried figs, while Peleg's model displayed the best fit for irradiated samples at 1 and1.5 kGy, and the Enderby model for those treated with 2 kGy. Results of Net isosteric heat of adsorption suggested that high irradiation dose increases the spontaneity of moisture adsorption. Hence, gamma irradiation exhibited a significant effect on the water specific surface area of which the magnitude was proportional to the increasingly applied doses. This effect was also visibly significant on the optimum water activity [aw (op)] for proper dried figs storage. Indeed, aw was about 0.4243 for control samples, which is much higher compared to irradiated ones (aw = 0.2). Information from this research suggests that gamma irradiation at dose up to 2 kGy extended the dried figs shelf life. Since many aspects related to the impact of gamma irradiation on the moisture adsorption isotherms and thermodynamic properties of dried figs as well as in other foods have yet to be further investigated, this study provides interesting results that may be a useful reference for future research direction.